Effects of Maternal Deprivation and Complex Housing on Rat Social Behavior in Adolescence and Adulthood - Kentrop, Jiska; Smid, Claire R.; Achterberg, E. J. M.; van IJzendoorn, Marinus H.; Bakermans-Kranenburg, Marian J.; Joëls, Marian; van der Veen, Rixt (Frontiers in Behavioral Neuroscience, 2018)
Early life context and stressful experiences are known to increase the risk of developing psychiatric disorders later in life, including disorders with deficits in the social domain. Our study aimed to investigate the influence of early life environment on social behavior in a well-controlled animal model. To this end we tested the effects of maternal deprivation (MD) on rat social play behavior in adolescence and social interaction in adulthood. Additionally, we provided a stimulating environment during adolescence (complex housing) as a potential intervention to diminish the effects of early life stress. Male and female Wistar rats were deprived from their mother for 24h on postnatal day 3 (PND 3) or were left undisturbed. Complex housing started 5 days after weaning and consisted of housing 10 same-sex conspecifics in large, two-floor MarlauTM cages until the end of the study. Social play behavior in adolescence was tested under different conditions (3h versus 24h social isolation prior to testing). Maternally deprived males –but not females– showed a longer latency to play and a decreased total amount of social play behavior, after the isolation period of 24h. In adulthood, social discrimination was impaired in deprived male and female rats in the three-chamber social approach task. Complex housing did not moderate the effects of MD, but in itself induced a strong behavioral phenotype. Both complex housed males and females hardly displayed any play behavior after a 3h isolation period. However, after 24h of isolation, these animals showed shorter latencies to engage in social play behavior. Only complex housed males truly showed more social play behavior here, while showing less social interest in adulthood. We conclude that MD has mild negative effects on social behavior in adolescence and adulthood, which are not counteracted by complex housing. Complex housing induces a specific phenotype associated with rapid habituation; falling asleep during the regular play session, while increasing play behavior after a prolonged period of isolation in adolescence, and less social interest, paired with intact social discrimination in adulthood. In both early life settings, males seem to be more influenced by the early life environment compared to females.